Designing with models : a studio guide to making and using architectural design models. - Mills, Criss B., ....- (Hoboken : Wiley, 2005)
Designing with Models, Second Edition is the revised, step-by-step guide to basic and advanced design process modeling. This comprehensive text explains the process from start to finish, and has been expanded to include up-to-date information on digital modeling programs and rapid prototyping processes. The impact of this new wave of 3D modeling technology is examined through interviews and numerous examples from renowned architects. Along with many new student projects, this new Second Edition features more than 800 high-quality photographs and fully illustrated in-depth case studies and the latest information on mastering the modeling of curvilinear components with planar material and casting techniques, exploring ideas with mixed media, working backwards from model information, recording and communicating 3D design work, exploring the safe and effective use of power tools, and more.
Keywords: Modelbouw